Coculture and Immobilization of Cellulolytic Bacteria for Enhanced Glucose Isomerase Production from Wheat Straw - Kognou, Aristide Laurel Mokale; Chio, Chonlong; Khatiwada, Janak Raj; Shrestha, Sarita; Chen, Xuantong; Zhu, Yuen; Ngane, Rosalie Anne Ngono; Agbor, Gabriel Agbor; Jiang, Zi-Hua; Xu, Chunbao Charles; Qin, Wensheng (Biotechnology and bioprocess engineering, 2023)
Coculture and whole-cell immobilization have myriad industrial applications for enhancing enzyme production. Using pretreated wheat straw as the sole carbon source, improving glucose isomerase production and cell growth by synthetic bacterial consortia was investigated. Thirteen cocultures were constructed based on the performance and antagonistic activities of monocultures from six cellulolytic soil bacteria. The performance of monocultures immobilized with calcium alginate was also tested. Only five cocultures (A, B, C, G and J) exhibited cell growth and enzyme production synergies. The highest level of synergism (15.17 U/mL) was found in coculture J composed of Mycobacterium sp. MKAL3 (4.06 U/mL) and Stenotrophomonas sp. MKAL4 (3.37 U/mL) with a synergism degree of 2.04. The synergism was unique to growth on wheat straw as it was completely absent in xylose-grown cocultures. The wheat straw degradation synergism could rely on specific compounds released by the MKAL3 strain that promote the activity of the MKAL4 strain and vice versa . However, immobilized strains MKAL1, MKAL2, MKAL3, MKAL4 and MKAL5 improved glucose isomerase production in the wheat straw fermentation process at different sodium alginate concentrations. Immobilization studies of purified glucose isomerases for hydrolysis and saccharification of wheat straw are now being conducted.